STUDY OF PROCESS PARAMETERS IN STIR CASTING METHOD FOR PRODUCTION OF PARTICULATE COMPOSITE PLATE - Dattatraya N. Lawate; Shriyash S. Shinde; Tushar S. Jagtap (International Journal of Innovations in Engineering Research and Technology, 2021)
Particulate composite is one of the promising materialsto fulfill the demands of modern technology. They find huge application inaerospace, automotive, structuraland marine industries.Particulate compositeconstituents ofa base materialcalled as matrixand other constituent is embeddedin matrix made of harder materialgenerally ceramic or non metallic materialcalled as reinforcement.Various processing techniques are available for manufacturing of particulate composites.Stir casting is one of the economical and extensivelyused methodsto enhance attractive properties of particulate composite.This paper presents an overview of stir casing process andprocess parameter havingAl alloy as a matrix phase and alumina (Al2O3) as a reinforcement.